Asymptotic Regulation of Time-Delay Nonlinear Systems with Unknown Control Directions - Radom Pongvuthithum (2018)
IEEE This paper studies the problem of global state regulation with stability for time-delay nonlinear systems with unknown control directions. Using a dynamic gain-based approach for counteracting time-delay nonlinearity and the Nussbaum-gain function for dealing with unknown control directions, we develop a dynamic state feedback control strategy that solves the problem. A novel construction of Lyapunov-Krasovskii functionals is presented and plays a key role in handling nonlinearity with delayed states and unknown control directions simultaneously. The proposed dynamic state feedback compensators are shown to guarantee: i) global asymptotic convergence of the system state to the origin; and ii) global boundedness of the resulted closed-loop systems